Adenoviral gene transfer of a u-PA receptor-binding plasmin inhibitor and green fluorescent protein: inhibition of migration and visualization of expression - Lamfers, M L; Wijnberg, M J; Grimbergen, J M; Huisman, L G; Aalders, M C; Cohen, F N; Verheijen, J H; van Hinsbergh, V W; Quax, P H (Thrombosis and haemostasis, 2000)
Smooth muscle cell migration plays a role in the development of intimal hyperplasia. Given the established role of the plasminogen activation system in cell migration, an approach to therapy is to overexpress an inhibitor of plasmin. Therefore, an adenoviral vector was constructed encoding the hybrid protein ATF.BPTI, which contains the active domain of bovine pancreas trypsin inhibitor (BPTI), fused to ATF, the amino terminal fragment or receptor-binding domain of u-PA. Adenoviral vectors expressing ATF and BPTI individually were also constructed, and a fourth vector was constructed encoding ATF.BPTI linked by an internal ribosomal entry site to Green Fluorescent Protein (ABIG). Both the expression and functionality of the recombinant proteins were established in human vascular smooth muscle cells. Adenoviral gene transfer of ATF.BPTI inhibited SMC migration more efficiently than the expression of ATF or BPTI individually. Expression of ABIG resulted in the co-expression of ATF.BPTI and Green Fluorescent Protein, thereby providing a tool to monitor transfection efficiency and the behavior of the transfected cells.